1904 Ohio Gen. and Local Acts 471, An Act Creating a Fish and Game Commission . . . §15 (vol. 97) - (:unkn) unknown (General Publisher, 1904)
No person shall hunt or shoot, or have in the open air for such purposes, any implements for hunting or shooting on any Sunday.
--
Keywords: HUNTING REGULATION